Political Interest and Academic Achievement among Students Offering Government in Senior Secondary School - Muraina, Kamilu Olanrewaju; Kehinde, Muraina Maruf; Omolara, Oladele (Universitas Pendidikan Ganesha, 2024)
Students do not realize their obligation to participate in the development of a society that can promote unity and peaceful coexistence within the nation in terms of political and societal interests. The purpose of this study was to analyze political interest and academic achievement among students offering Government in senior secondary school. Five hundred participants constituted the study’s sample out of which only 478 were used after data administration. Both the independent and dependent variables were measured with validated instruments with 0.85 and the data obtained was analyzed using Pearson Product Moment Correlation (PPMC) Statistical method. Two research hypotheses were formulated and tested at 0.05 level of significance. The result showed that there was significant relationship between political interest and Students’ academic performance in Government (r= .777; p<0.05) as well as between political interest and Students’ attitudes to Government (r= .548; p<0.05). The implication of this showed that political interest had significant influence on academic achievement among students offering Government in senior secondary school. In view of these findings, it was recommended that educational stakeholders should intensify their effort to organize workshops on the implications of political interest on academic achievement among students offering Government in senior secondary school.